2012
DOI: 10.1080/1943815x.2012.691884
|View full text |Cite
|
Sign up to set email alerts
|

Regional non-CO2greenhouse gas fluxes inferred from atmospheric measurements in Ontario, Canada

Abstract: Independent verification of bottom-up greenhouse gas (GHG) emission inventories is crucial for a reliable reporting of Kyoto gases to the United Nations Framework Convention on Climate Change. Here, we use a pseudo-data experiment to test if our improved version of the well-known Radon tracer method (RTM) is able to quantitatively retrieve regional GHG fluxes. ). Using a Stochastic Time-Inverted Lagrangian Transport (STILT) model this difference can be attributed to an overestimation of CH 4 emissions in a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…These deviations appear to reflect the spatial patterns in source activity that are well represented in ACES, particularly line source emissions from major roads, but that are not captured by the population-and nightlightsbased downscaling in ODIAC. While ODIAC and the other global inventories were not designed to be used for this type of urban analysis, they have been applied to a wide range of urban-and regional-scale modeling and policy analyses (e.g., Brioude et al, 2013;Hakkarainen et al, 2016;Marcotullio et al, 2012;Sarzynski, 2012;Schneising et al, 2013;Shiga et al, 2014;Tohjima et al, 2014;Turnbull et al, 2011;Vogel et al, 2012;Wunch et al, 2009;Yadav et al, 2016). Indeed, the high-resolution grids of these inventories (1-10 km) appear to Journal of Geophysical Research: Atmospheres 10.1002/2017JD027359 imply a fidelity at these local scales that is not necessarily evident.…”
Section: Discussionmentioning
confidence: 99%
“…These deviations appear to reflect the spatial patterns in source activity that are well represented in ACES, particularly line source emissions from major roads, but that are not captured by the population-and nightlightsbased downscaling in ODIAC. While ODIAC and the other global inventories were not designed to be used for this type of urban analysis, they have been applied to a wide range of urban-and regional-scale modeling and policy analyses (e.g., Brioude et al, 2013;Hakkarainen et al, 2016;Marcotullio et al, 2012;Sarzynski, 2012;Schneising et al, 2013;Shiga et al, 2014;Tohjima et al, 2014;Turnbull et al, 2011;Vogel et al, 2012;Wunch et al, 2009;Yadav et al, 2016). Indeed, the high-resolution grids of these inventories (1-10 km) appear to Journal of Geophysical Research: Atmospheres 10.1002/2017JD027359 imply a fidelity at these local scales that is not necessarily evident.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that a simple per capita distribution of residential emissions is non-sufficient is applicable to any site in proximity to major urban centres. Other studies found similar results when investigating urban CH 4 emissions (Vogel et al, 2012). The possible influence of the simplified linking of emissions and transport should caution anyone working with observational datasets that are close to large facilities that emit from stacks.…”
Section: Discussionmentioning
confidence: 52%
“…3), and found a 75% increase of the night-time FFCO 2 fluxes during winter, using the radon-tracer method (e.g. Levin et al, 1999;Hammer and Levin, 2009;Vogel et al, 2012) in our domain. A similar seasonal variation of the FFCO 2 fluxes was also found by Levin et al (2003).…”
Section: Continuous Proxy-based Ffcomentioning
confidence: 55%
“…Due to its physical characteristics, presented in classical literature such as Fleischer et al . [], Tanner [], Nazaroff and Nero [], Nazaroff [], and Porstendorfer [], the radioactive noble gas 222 Rn is widely used by the scientific community to study a number of different research topics, such as (i) to improve inverse transport models, which are used to calculate emissions of greenhouse gases (GHGs) [ Biraud et al ., ; Hirao et al ., ; Locatelli et al ., ]; (ii) to study atmospheric transport and mixing processes within the planetary boundary layer [ Zahorowski et al ., ; Galmarini , ; Vinuesa et al ., ; Baskaran , ; Chambers et al ., , ; Williams et al ., , ; Grossi et al ., ; Vogel et al ., ; Hernández‐Ceballos et al ., ; Vargas et al ., ]; (iii) to improve radon flux inventories [ Szegvary et al ., ; Griffiths et al ., ; López‐Coto et al ., ; Karstens et al ., ]; (iv) to experimentally estimate GHGs fluxes by using the Radon Tracer Method [ Levin et al ., ; Vogel et al ., ; Wada et al ., ; Grossi et al ., ]; (v) to understand the influence of climate change on the atmospheric radon increase and its associated health risks [ Nazaroff , ; Bochicchio et al ., ; Bossew et al ., ]; and (vi) to refine baseline selection and characterization techniques and analyze air mass history and fetch at remote sites [ Zahorowski et al ., ; Chambers et al ., , , ].…”
Section: Introductionmentioning
confidence: 98%